KEPUASAN SISWA TERHADAP PENGGUNAAN GOOGLE CLASSROOM SEBAGAI MEDIA PEMBELAJARAN PENJAS SMP NEGERI 18 PONTIANAK - Gunawan, Edi; Triansyah, Andika; Hidasari, Fitriana Puspa (Universitas Tanjungpura, 2022)
AbstractDistance learning during the COVID-19 pandemic poses several obstacles for students, especially in physical education subjects. Learning solutions that can be used to support the learning process are online. One of the platforms used in the online learning process is Google Classroom which contains features that support so that teaching and learning activities are more effective. This research is a descriptive research conducted by survey method and the instrument used is a questionnaire. The purpose of this study was to determine student satisfaction with the use of google classroom as a physical education learning medium during the covid-19 pandemic, the subjects of this study were class VIII students at SMP Negeri 18 Pontianak. Test the validity of the instrument using Product Moment Correlation and test the reliability of the instrument using the Alpha Cronbach formula through SPSS V25. The validity coefficient is 0.374 and the coefficient is 0.942 and to analyze the data used quantitative descriptive techniques with percentages. Based on the results of research conducted by researchers with a total population of 203 people while those who answered the questionnaire were 139 people, the following results were obtained: there were 11 students (7.91%) in the